Squamous cell carcinoma complicating donovanosis not a thing of the past!. (October 2014) - Sethi, Sumit; Sarkar, Rashmi; Garg, Vijay; Agarwal, Shipra
Donovanosis causes granulomatous ulceration of genitalia and neighbouring sites with little tendency to heal spontaneously. It is uncommonly seen nowadays in sexually transmitted infection clinics of north India. The present case is reported for its scarcity and to make clinicians aware of this disease which may rarely accompany carcinoma.